Overweight and obesity in teachers - Rodríguez-Guzmán, Lucía (2006)
Objetive: To determine overweight and obesity levels in teachers of Guanajuato, Mexico. Design: Observational, transversal, retrospective study. Setting: Labor Investigation Institute, Faculty of Medicine, Guanajuato University. Participants: Four hundred and seventy-nine teachers (208 men and 271 women). Interventiones: Anthropometric indicators including weight, height, waist circumference and body mass index were calculated to estimate body fat. Main outcome measures: Overweight and obesity in teachers. Results: The prevalence of overweight and obesity was 45% and 21%, respectively. Conclusions: Overweight and obesity are important risk factors for cardiovascular disease. Teachers need a healthy diet and physical activity promotion.